Cross‐cultural Information Access. Issue 1 (14th October 2022) - Choi, Inkyung; Lee, Wan‐Chen; Liu, Ying‐Hsang; Chen, Hsinliang; Oard, Douglas W; Oh, Chi Young
Abstract: Despite the advanced information technology's impact on the extent and availability of digital information, information access is not equally attainable to everyone. The lack of cultural and linguistic diversity in information systems and infrastructure has raised concerns over limited access to digital information, which also harms the information environment. For example, a flood of misinformation and disinformation during the pandemic rendered misrepresentation of cultures and fed the fear of people from different cultures. The "deep learning" revolution has enabled advances in cross‐language search technology and in automated translation of content from one language to another, but the lowering of linguistic barriers to information access, in turn, serves to highlight the need for a comparable degree of focus on cultural differences. The proposed panel will discuss cultural and linguistic diversity as manifested in various information systems and infrastructures and review past and current information systems and practices either lacking or supporting cultural and linguistic diversity.